2004
DOI: 10.1590/s1415-790x2004000400008
|View full text |Cite
|
Sign up to set email alerts
|

A mortalidade materna nas capitais brasileiras: algumas características e estimativa de um fator de ajuste

Abstract: A mortalidade materna pode ser considerada um excelente indicador de saúde, não só da mulher, mas da população geral; mostra, também, iniqüidades. A redução da mortalidade materna é uma das principais metas, estando também incluída nas Metas do Desenvolvimento do Milênio da ONU. OBJETIVO: Conhecer a qualidade da informação da mortalidade de mulheres de 10 a 49 anos, e estimar a razão de mortalidade materna (RMM) e os fatores de ajuste para os dados oficiais, no conjunto das capitais de estados brasileiros e Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
54
1
102

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(159 citation statements)
references
References 5 publications
2
54
1
102
Order By: Relevance
“…4 However, the current study identified an almost 50% difference between Metropolitan and Sertão regions over the period. 5 The historically lower level of maternal mortality in Metropolitan region compared with other regions might explain why it has been easier to reduce maternal levels in Sertã o and Mata/ Agreste regions.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…4 However, the current study identified an almost 50% difference between Metropolitan and Sertão regions over the period. 5 The historically lower level of maternal mortality in Metropolitan region compared with other regions might explain why it has been easier to reduce maternal levels in Sertã o and Mata/ Agreste regions.…”
Section: Discussioncontrasting
confidence: 50%
“…4 Misclassification of maternal deaths generally depends on the quality of national and local vital statistics and in particular, on the commitment and awareness of physicians reporting the presence of a recent pregnancy in a death certificate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…É interessante comparar os estudos de Sousa et al 13 e Laurenti et al 14,15 , que exploraram a mortalidade materna no mesmo período (2002), com diferentes metodologias. Os valores de RMM não ajustadas foram semelhantes, mais elevados no estudo de Souza et al 13 , e destacando-se o pior desempenho da Região Nordeste.…”
Section: Discussionunclassified